Some foliicolous loculoascomycetes from India - PATIL, CHANDRAHAS R. (Indian Phytopathology, 2002)
Twelve foliicolous loculoascomycetes are reported on new hosts from India. These are: Chatetoplaca memecyli on Eugenia stocksii, Chaetothyrina molliscula on Diospyros candolleana, C. hirtellae on Luvunga eleutherandra, Chaetothyrium acalyphae on Eugenia jambolana, C. premixtum on Olea dioica and Heptage benghalensis, C. variabile on Carissa congesta and Eugenia stocksii, Dictyothyrium ocoteae on Embelia robusta, Lembosia pavettage on Canthium umbellatum, Microcallis ceibae on Gymbosporia montana, Microthyrium paraguayense on Olea dioica, Chaetothyrina melagopora var. indica on Memecylon umbellatum and Stomiopeltis aspera on Salacia oblonga.